The Anomaly Flow over Riemann Surfaces. (9th April 2019) - Fei, Teng; Huang, Zhijie; Picard, Sebastien
Abstract: We initiate the study of a new nonlinear parabolic equation on a Riemann surface. The evolution equation arises as a reduction of the Anomaly flow on a fibration. We obtain a criterion for long-time existence for this flow, and give a range of initial data where a singularity forms in finite time, as well as a range of initial data where the solution exists for all time. A geometric interpretation of these results is given in terms of the Anomaly flow on a Calabi–Yau three-fold.